2016
DOI: 10.3390/recycling1010194
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Antioxidant Phenolics from Agri-Food Waste Biomass Using a Newly Designed Glycerol-Based Natural Low-Transition Temperature Mixture: A Comparison with Conventional Eco-Friendly Solvents

Abstract: A novel natural low transition temperature mixture (LTTM), composed of glycerol and ammonium acetate (molar ratio 3:1), was tested for its efficacy as a solvent in recovering phenolics from chlorogenate-rich agri-food solid wastes, including potato peels (PPs), eggplant peels (EPPs), and spent filter coffee (SFC). The efficacy of this solvent was compared with other eco-friendly solvents, including aqueous glycerol, aqueous ethanol, and water. The LTTM was demonstrated to be by far the most efficient in extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 32 publications
1
30
1
Order By: Relevance
“…On the contrary, the extract obtained with the LTTM displayed significantly lower A AR and P R (p < 0.05), compared with the aqueous methanolic extract (Figure 3). This finding contrasted a general trend observed in studies on LTTM extracts, where increased polyphenol levels were associated with proportional antioxidant activity [5,9,23], but such a phenomenon has been previously seen in OLL extracts, with correlation between Y TP and A AR being low and statistically non-significant [7]. In concurrence with this, a more recent study showed that high Y TP did not fully coincide with high A AR in OLL extracts [25].…”
Section: Assessment Of Model Validity and Extraction Efficiencycontrasting
confidence: 53%
See 1 more Smart Citation
“…On the contrary, the extract obtained with the LTTM displayed significantly lower A AR and P R (p < 0.05), compared with the aqueous methanolic extract (Figure 3). This finding contrasted a general trend observed in studies on LTTM extracts, where increased polyphenol levels were associated with proportional antioxidant activity [5,9,23], but such a phenomenon has been previously seen in OLL extracts, with correlation between Y TP and A AR being low and statistically non-significant [7]. In concurrence with this, a more recent study showed that high Y TP did not fully coincide with high A AR in OLL extracts [25].…”
Section: Assessment Of Model Validity and Extraction Efficiencycontrasting
confidence: 53%
“…Total polyphenol yield (Y TP ) was determined with the Folin-Ciocalteu methodology [8] and results were expressed as mg caffeic acid equivalents (CAE) per g of dry weight. Total flavonoid yield (Y TFn ) was assayed with AlCl 3 reagent, as previously reported [9] and given as mg rutin equivalents (RtE) per g of dry weight. The antioxidant activity was estimated by determining the antiradical activity (A AR ) and the ferric-reducing power (P R ) of the extracts.…”
Section: Sample Preparation and Determinationsmentioning
confidence: 99%
“…Yield in total polyphenol (Y TP ) was determined with the Folin-Ciocalteu methodology, as described elsewhere [14]. Yield in total flavonoids (Y TFn ) was determined according to a previously published protocol [15]. The antiradical activity (A AR ) and reducing power (P R ) were determined with well-established methods [16].…”
Section: Sample Preparation and Determinationsmentioning
confidence: 99%
“…Total flavonoid yield (Y TFn ) was assayed with AlCl 3 reagent, as previously reported [12] and given as mg rutin equivalents (RtE) per g of dry weight. Yield in total flavanols (Y TF ) was measured as µg catechin equivalents (CtE) per g of dry weight, following derivatization with DMACA reagent [17].…”
Section: Determinationsmentioning
confidence: 99%
“…Recent investigations with LTTMs composed of glycerol or L-lactic acid (HBD) and sodium acetate (HBA), two low-cost biomolecules, have shown that polyphenol extraction yields were much higher than those obtained with water and were comparable to those obtained with aqueous ethanol [12,13]. On such grounds, the study was carried out to screen combinations of L-lactic acid used as HBD, with the natural amino acids glycine and L-alanine, but also choline chloride, as HBAs ( Figure 1) in an effort to identify (i) pairs that provide stable LTTMs and (ii) LTTMs that can afford high extraction yields of antioxidant phenolics from ICSWs.…”
Section: Introductionmentioning
confidence: 99%